2020
DOI: 10.3390/ijerph17113880
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Body Composition Changes after Preseason Training in Elite Handball Players

Abstract: The purpose of this study was to evaluate changes in the estimated body composition of elite female and male Polish handball players during a five-week preseason training camp. Height and weight were measured, while body composition was estimated with bioelectrical impedance in 18 male and 17 female handball players before and after the five-week training protocol. Components of body composition included total body water (TBW), fat-free mass (FFM), muscle mass (MM), and absolute and relative fat mass (FM). Wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
2
9
0
2
Order By: Relevance
“…The overall analysis of the pattern for a top handball player found that the average height was 1.926 m with optimal limits between 1.86 m and 2 m; the weight average was 95.28 kg with 86 to 105 kg accepted limits; and the average BMI was 25.677 with recommended limits between 24 and 27.3. We also obtained statistical significance for p < 0.001 (height) and p < 0.0001 (weight and BMI) (Figure 1) [14,[47][48][49]67,68]. We consider the identified pattern in our study for each playing position valid as, in 16 out of 18 situations, we obtained statistical significance at linear regression, and the data were collected for a period of almost 20 years from 974 top male handball players (Figure 2).…”
Section: Discussionmentioning
confidence: 76%
“…The overall analysis of the pattern for a top handball player found that the average height was 1.926 m with optimal limits between 1.86 m and 2 m; the weight average was 95.28 kg with 86 to 105 kg accepted limits; and the average BMI was 25.677 with recommended limits between 24 and 27.3. We also obtained statistical significance for p < 0.001 (height) and p < 0.0001 (weight and BMI) (Figure 1) [14,[47][48][49]67,68]. We consider the identified pattern in our study for each playing position valid as, in 16 out of 18 situations, we obtained statistical significance at linear regression, and the data were collected for a period of almost 20 years from 974 top male handball players (Figure 2).…”
Section: Discussionmentioning
confidence: 76%
“…58.7%). Cichy et al (2020) found the mean somatic parameters of Polish female handball players (height 176.3 cm, weight 70.6 kg, BMI -22.8 kg m −2 , FM BIA -19.1%, FFM BIA -56.9 kg, TBW BIA -59.1%).…”
Section: Discussionmentioning
confidence: 90%
“…Excessive adipose tissue acts as a dead weight in activities where the body mass must be repeatedly lifted against gravity during locomotion and jumping (Reilly, & Doran, 1996). Studies of various authors deal with somatic characteristics and their relation to performance not only in males, but also in females (Carvalho, Mourão, & Abade, 2014;Cichy et al, 2020;Chaouachi et al, 2009;Čavala et al, 2008;Malá, Malý, Záhalka, & Bunc, 2010;Malá, Malý, Zahálka, Tůma, & Bunc, Malá, 2011;Malý, Zahálka, Tůma, & Teplan, 2012;Milanese et al, 2011;Rogulj et al, 2005;Šibila, & Pori, 2009;Visnapuu & Jürimäe, 2009 etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…Body composition is usually analyzed through anthropometric measurement of weight, skinfolds, circumferences, diameters, heights and BMI [31]. Body size is of great importance for throwing in attack or blocking in defense, achieving higher ball velocity in jump throwing also having a strong positive effect on throwing performance and isometric strength [14,32]. The presence of a high percentage of fat is associated with multiple diseases and inflammation, so it has negative health consequences [6].…”
Section: Introductionmentioning
confidence: 99%